VisTCR: An Interactive Software for T Cell Repertoire Sequencing Data Analysis - Ni, Qingshan; Zhang, Jianyang; Zheng, Zihan; Chen, Gang; Christian, Laura; Grönholm, Juha; Yu, Haili; Zhou, Daxue; Zhuang, Yuan; Li, Qi-Jing; Wan, Ying (Frontiers in Genetics, 2020)
Recent progress in high throughput sequencing technologies has provided an opportunity for researchers to probe T cell receptor (TCR) repertoire deeply, which brought explosive accumulation of T cell receptor sequencing data. Favorable bioinformatics tools are required to meet the demand of the related analysis task. Here VisTCR is introduced, which is a web based tool for TCR sequencing data management and analysis. VisTCR has a data storage module for collecting raw sequencing data files and making them inspection convenient. VisTCR also integrates some useful TCR parsing and analyzing methods, such as identifying gene segments from raw fastq files, visualizing clonotype distribution, diversity and similarity, performing statistical analysis, and tracking individual clones, et al. For ease of use, VisTCR provides an interactive interface that users can access all the TCR analysis methods by pointing and clicking on the interface and the results can be downloaded as tables or graphs in the process of analysis. In brief, VisTCR is an efficient, comprehensive, and user-friendly TCR sequencing data management and analysis tool. The source code is freely available at https://github.com/qingshanni/VisTCR.